2016
DOI: 10.1002/etc.3262
|View full text |Cite
|
Sign up to set email alerts
|

The derivation of effects threshold concentrations of lead for European freshwater ecosystems

Abstract: The main objective of the present study was to derive ecologically relevant effect threshold concentrations of (dissolved) Pb for selected European Union (EU) freshwater rivers, using the 2008 EU Voluntary Risk Assessment Report as a starting point and more advanced methodologies than those used in the Voluntary Risk Assessment Report. This included 1) implementing more robust quality criteria for selecting chronic toxicity data; 2) the conversion of total to dissolved Pb concentrations using a combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 46 publications
(98 reference statements)
0
52
1
Order By: Relevance
“…by Robles‐Vargas and Snell . Esbaugh et al called the same strain P. rapida, and it was called P. rapida by van Sprang et al in their paper seeking to determine ecologically relevant effect thresholds for dissolved lead pollution in freshwaters. Nys et al noted the taxonomic uncertainty associated with this Philodina species as they produced data to develop a bioavailability model for lead.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…by Robles‐Vargas and Snell . Esbaugh et al called the same strain P. rapida, and it was called P. rapida by van Sprang et al in their paper seeking to determine ecologically relevant effect thresholds for dissolved lead pollution in freshwaters. Nys et al noted the taxonomic uncertainty associated with this Philodina species as they produced data to develop a bioavailability model for lead.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Nys et al tested chronic toxicity of lead to the monogonont rotifer Brachionus calyciflorus in 5 natural waters, and recorded a population growth rate EC50 of 180 µg lead/L with 95% CL of 168–192. Ecologically relevant effect thresholds for dissolved lead pollution in freshwaters were determined by van Sprang et al to be 6.3–31.1 µg/L, calculated to protect about 95% of freshwater species.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the toxicity of metals has been shown to be highly dependent on the physicochemistry of the receiving environment, such as pH, DOC, or hardness [19,20]. The BLMs allow a prediction of metal toxicity in water with a specific chemical composition, and thus site-specific environmental thresholds (e.g., 5% hazard concentration [HC5] values), can be derived [24,25]. The BLMs allow a prediction of metal toxicity in water with a specific chemical composition, and thus site-specific environmental thresholds (e.g., 5% hazard concentration [HC5] values), can be derived [24,25].…”
Section: The Current Regulatory Situation and The Need For Bioavailabmentioning
confidence: 99%
“…For a wide range of elements it has been shown that the bioavailability tends to decrease when they are bound to organic matter, e.g. Pb (Van Sprang et al, 2015), U (Trenfield et al, 2011a, b), Ni (Weng et al, 2004;Deleebeeck et al, 2009), Cu (Deruytter et al, 2014) and Zn (De Schamphelaere et al, 2005). In addition, it is possible that the plants are able to regulate the uptake and/or disposal of certain elements.…”
Section: A Hotspot For Transfer Of Pollutants To Biota?mentioning
confidence: 99%